INFLUENCE OF EMOTIONAL INTELLIGENCE OF ELITE WOMEN’S HANDBALL PLAYERS ON THE CHOICE OF STRESS COPING STRATEGIES - Tetiana V. Petrovska; Lilia V. Arnautova; Borys I. Palamar; Irene V. Khmelnitska; Svitlana V. Fedorchuk; Tetiana M. Bulhakova; Iryna O. Kohut (Клінічна та профілактична медицина, 2023)
Introduction. The problem of finding optimal strategies for overcoming stress by elite athletes remains relevant. Many authors study the problem of stress resistance in sports from the standpoint of forming a set of athlete’s personal qualities. The emotional intelligence is such athlete’s personal characteristics that affect the ability to withstand competitive stress.